UTILIZATION OF INFORMATION SOURCES BY PROGRESSIVE AND NON-PROGRESSIVE FARMERS OF KARNATAKA STATE - D. SRINIVASA CHARY, K. V. PATIL, I. S. RAO, M. SREENIVASULU, G.E.CH. VIDYA SAGAR and (The Journal of Research, PJTSAU, 2020)
Information sources are the various means by which a piece of information is recorded for use by an individual. It is how a person is informed about something or knowledge is availed to someone or a group of people. Patel et al., (1993) have suggested that in a developing country like India, dissemination of agricultural information and improved technology through the use of latest communication technology can play a great role in agricultural development. Knowledge derived from formal research, or developed in other localities, can stimulate new thinking and practices (Figueroa et al., 2002). So it is evident that proper dissemination of information is highly necessary for agriculture development.